Identification of the municipal water-steam network, elaboration of its computer controlled system - Szakonyi, Lajos (Acta Agraria Kaposváriensis, 2006)
The presentation introduces a project utilizing the new information and communication technology in a regional perspective and its objective is to elaborate the control-, expert- and decisionmaking support-system in the city’s water-steam network informatics network in the interest of reduction of power loss. The applied research activity is aimed at the completion of the experimental identification of the energy-current network utilizing the infocommunication technology to be developed and the definition of the control strategy ensuring energy-saving operation based on the assessment of computer simulation.